The Role of Marketing 4P Towards Brand Decision of Cigarette Products in Millennial & Z Generations in Jambi City Mediated by Perception - Christoforus Chandra Dewanto; Prio Utomo (Fakultas Ekonomi Dan Bisnis Universitas Pelita Harapan, 2022)
The Ministry of Finance has issued PMK Number 192/PMK.010/21 concerning “Tobacco Products Excise Tariffs”, the regulation regulates the determination of cigarette excise rates and retail selling prices (HJE). One of the reasons for the government to increase the excise rate on tobacco products is to make people reduce their cigarette consumption. This research focuses on the consumption of cigarettes by several generations in Jambi City, namely Generation X who was born in the vulnerable years between 1965 – 1980, the Millennial Generation who were born in the age range of 1981 – 1996 and Generation Z who was born in the age range of 1997 – 2012. from this study to determine whether public perception of cigarettes can be influenced by the 4P marketing theory (Product, Price, Place and Promotion) which is widely applied by cigarette companies to determine which brand of cigarette products they will consume. The method used in this study is descriptive analysis with a quantitative approach, with data analysis techniques Partial Least Square Structural Equation Modeling or PLS-SEM using Smart PLS 3.2 software. The results showed that of the 4 variables of the 4P theory applied by cigarette companies, only 1 variable, namely Price, had no direct and significant effect on people's perceptions of cigarettes. Other variables, namely Product, Place and Promotion have a direct and significant effect on people's perceptions of cigarettes in influencing people's decisions to consume products from a brand. This research still has some limitations, namely the research has not been too broad to all outlets and respondents who can represent all segments of society, and also research can be focused on one cigarette manufacturer. This research can be used by cigarette manufacturers in determining the company's promotional policies so that it can be more targeted in accordance with its target market.